Pliocene-Quaternary crustal melting in central and northern Tibet and insights into crustal flow - Qiang Wang (Nature Portfolio, 2016)
The role of the low velocity-high conductivity zones (LV–HCZs) in developing the Tibetan Plateau has remained controversial. Here, Wang et al.present new geochemical and petrological data that show the LV–HCZs are sources of partial melt thus giving insight into the development of the Tibetan Plateau.